Innovative Technology as Base Arms of Modernization of the State Local Administration - S Mukhtаrovа K.; R., Mouly P.; A, Myltykbayeva A.; E, Mukhtar E. (Farabi Journal of Social Sciences, 2019)
Abstract. Modernization of the system of state local administration (SLA) and local self-administration (LSA) in the Republic of Kazakhstan is connected with the applying of innovations that are both organizational, structural, financial and institutional. Reforms in the sphere of SLA and LSA suggest an approach requiring the improvement of the state local administration on the basis of system of innovative technologies. The article discusses the new management model which contains the elements of market mechanisms, gradually replacing the old administrative-bureaucratic model.